Spinal fusion in girls with Rett syndrome: post‐operative recovery and family experiences. (9th March 2015) - Marr, C.; Leonard, H.; Torode, I.; Downs, J.
Abstract: Background: Rett syndrome is a severe neurodevelopmental disorder mainly affecting females and scoliosis is a common co‐morbidity. Spinal fusion may be recommended if the scoliosis is progressive. This qualitative study investigated recovery of girls with Rett syndrome during the first 12 post‐operative months and explored family perspectives and coping around the time of surgery. Method: Parents registered with the population‐based Australian Rett Syndrome Database were recruited to this study if their daughter had a confirmed pathogenic MECP2 mutation and spinal fusion between 2006 and 2012. Twenty‐five interviews were conducted to determine their daughter's recovery and parental stresses and coping. Themes in the interview data were identified with content analysis, and the regaining of gross motor skills over the first 12 post‐operative months was described with time‐to‐event (survival) analysis. Results: Pain and energy levels, appetite, mood and coinciding health issues influenced their daughter's post‐operative recovery. The majority of girls recovered preoperative sitting (88%), standing (81%) and walking (80%) by 12 months. The decision to proceed with surgery was associated with feelings of fear, obligation, relief and guilt for families. Development of complications, poor support and feelings of isolation increased their emotional burden whereas adequate information and discharge preparation, confidence in self and staff, and balancing personal needs with their daughter's care relieved this burden. Interpretation: Our study identified clinical practice issues in relation to families whose daughter with Rett syndrome undergoes spinal fusion, issues that are also relevant to other severe disabilities. Return of wellness and gross motor skills following spinal fusion in girls with Rett syndrome occurred within the first 12 post‐operative months in most cases. Parents require information and practical support to alleviate their emotional burden.